The Influence of Product Packaging Design and Social Media Advertising on Purchase Intention : (Study on Users of Kahf Branded Care Products) - Arif Ahmad Dhani; Mahrinasari Mahrinasari; Dwi Asri Siti Ambarwati (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this study is to analyse the influence of men's awareness of their skincare and appearance, as well as the development of the skincare industry specifically for men, such as the Kahf brand. This research uses a quantitative approach with data collection through distributing questionnaires to 112 respondents. The analysis method in this study was carried out with the help of SPSS software ver. The results showed that product packaging design and social media advertising have a positive and significant influence on the purchase intention of Kahf products. These findings provide important insights for skincare and marketing companies in designing effective product design and social media advertising strategies to increase consumer purchase intentions. In addition, this study also highlights the importance of considering other factors that may influence purchase intention, which could be the subject of further research.